(3GdHjGf hGdJHjfs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3NWHI YJHI Hf ZRhGf GdSdei QMeg Gddg MeOkG ddg hCKfi Ydjg hUdi Ydi GdfHi Udi Gddg Ydjg hSde Ke bGd CeG HYO aEf GdOfjG bO hdJ MPGA s
(3BNQgG (B:s
(3aYQag gTGe HUhQI GdgLGA hde jYQag GdCYQGHi hcGf Ydjg NeSI ced GdSaQ GdKGdK hjJdhg Ef TGA Gddg ai Ch GdQGHY (B: (3JhGO GdCYQGH s
(3GdfSNI HgG MhGTs
(3cJHJ HGdfSNI Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdCOHs